Contemporary Environmental and Mathematics Education Modelling Using New Geometric Approaches Geometries of Liberation (Springer International Publishing, 2018)
This book takes a fresh approach to using educational tools to solve profound problems in societies. The authors bring perspectives from curriculum studies, mathematics education, environmental education, and Indigenous epistemologies to a new consideration of "geometries to think with". These tools reveal the wealth of resources and interrelationships in our world that have the potential to reconfigure and revitalize education. The transdisciplinary nature of the chapters and authors emphasizes the need for thinking beyond boundaries, while respecting the wisdom inherent in intellectual disciplines and traditions.